2018
DOI: 10.1177/1541931218621280
|View full text |Cite
|
Sign up to set email alerts
|

Pokémon Go as a Tool to Study the Social and Cognitive Factors that Impact Spatial Navigation

Abstract: Researchers in spatial navigation have the difficult task of finding ecologically valid measures while maintaining a reasonable degree of internal validity. This often means simulating wayfinding and navigation task in the laboratory which increases control but eliminates the experience of walking around a natural environment. Augmented reality games like Pokémon Go allow researchers a novel way to study individual differences in cognitive and social factors in wayfinding with a game already designed to motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…For instance, active exploration of an environment is reported to be highly beneficial to children, if elements of gamification such as finding motivational objects are introduced into the task while exploring the environment (Fornasari et al, 2013;Proulx et al, 2016). A recent study on the PokemonGo R game also revealed that greater curiosity elicited by the game increased the quality of the spatial representation of the environments explored by the children (Blasko et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, active exploration of an environment is reported to be highly beneficial to children, if elements of gamification such as finding motivational objects are introduced into the task while exploring the environment (Fornasari et al, 2013;Proulx et al, 2016). A recent study on the PokemonGo R game also revealed that greater curiosity elicited by the game increased the quality of the spatial representation of the environments explored by the children (Blasko et al, 2018).…”
Section: Discussionmentioning
confidence: 99%